Cancans, croissants, and caskets - McHugh, Mary (McHugh, Mary. Happy Hoofers mystery., 2015)
"It's Bastille Day in Paris. The Happy Hoofers--Tina, Janice, Pat, Mary Louise, and Gini--are all set to kick off the fete by dancing the cancan on a beautiful sightseeing cruise down the Seine. As the leggy ladies soak in the magic of the city of lights, everything is magnifique...until a very important patron goes belly-up on the top deck. On the heels of their French debut, murder takes center stage. The five daring dancers will need to step lively to stop the crafty killer fast...or their grand finale will turn out far more explosive than the fireworks over the Eiffel Tower" --